Толерантність до невизначеності як чинник успішності виконання професійних завдань поліцейськими в умовах війни - Шиліна, А. А.; Shylina, A. A.; Шиліна Алла Андріївна (Перспективи та інновації науки. - 2024. - № 5(39). - С. 940-951, 2024)
Виявлено вплив толерантності до невизначеності на успішність виконання професійних вимог поліцейськими в ході здійснення професійної діяльності в умовах воєнного стану. Наведено результати дослідження поведінки та переживання, пов'язаних з роботою у поліцейських з високим та низьким рівнем толерантності до невизначеності. Показано, що поліцейські з високим рівнем толерантності до невизначеності мають більшу схильність до професійних домагань, вони ставлять більш високі цілі та прагнуть професійного росту, більше віддаватися роботі у порівнянні з поліцейськими з низьким рівнем толерантності до невизначеності. Кореляційний аналіз показав, що задоволеність своїми професійними досягненнями буде тим більше, чим більше поліцейські толерантні до невизначеності.

The police play a key role in ensuring public order and security in the subordinated territory. During martial law, its functions may change depending on the specific situation and the decisions of the authorities. In addition to their direct duties, police officers have to participate in the coordination of the evacuation of people from dangerous areas and provide assistance in rescue operations, the police take part in the protection of important objects, take part in military operations, in particular in counter-terrorist actions or in operational actions against armed groups . This leads to the fact that police officers feel constant stress, which affects their ability to perform professional duties, their attitude to the service and their lives. Police work often requires quick and adaptive responses to unforeseen situations, where tolerance for uncertainty plays an important role in the ability to work effectively in environments where information or circumstances are unclear or changing. Tolerance for uncertainty can include the ability to quickly assess a situation, make decisions based on limited information, and adapt to change. The article presents the results of a study of work-related behavior and experiences of police officers with high and low levels of uncertainty tolerance. It is shown that police officers with a high level of tolerance for uncertainty are more prone to professional harassment, they set higher goals and strive for professional growth, have a greater tendency to professional harassment, and are more likely to devote themselves to work compared to police officers with a low level of tolerance for uncertainty. Correlation analysis showed that satisfaction with their professional achievements will be greater, the more police officers are tolerant of uncertainty. Life activity in the professional life of police officers with a high level of tolerance for uncertainty depends on their attitude to the new, difficult tasks they face and their attitude to uncertain situations. The increase in willingness to give all one's strength to the performance of professional tasks depends on the preference for uncertainty in the professional activity of police officers.

Выявлено влияние толерантности к неопределенности на успешность выполнения профессиональных требований полицейскими в ходе осуществления профессиональной деятельности в условиях военного положения. Представлены результаты исследования поведения и переживания, связанных с работой у полицейских с высоким и низким уровнем толерантности к неопределенности. Показано, что полицейские с высоким уровнем толерантности к неопределенности имеют большую склонность к профессиональным притязаниям, они ставят более высокие цели и стремятся к профессиональному росту, больше отдаваться работе по сравнению с полицейскими с низким уровнем толерантности. Корреляционный анализ показал, что удовлетворенность своими профессиональными достижениями будет тем больше, чем больше полицейские толерантны к неопределенности.
Tolerance to uncertainty as a factor of successful performance of professional tasks by police officers in war conditions
Keywords: толерантність до невизначеності; поліцейські; професійна діяльність; умови війни; переживання пов’язані з роботою; tolerance for uncertainty; police officers; professional activity; war conditions; work-related experiences; толерантность к неопределенности; полицейские; профессиональная деятельность; условия войны; переживания связанные с работой